American Polka in the Media: From Next to Nothing to 24/7 - Richard March (Transatlantica)
From its very inception as a nineteenth century popular culture fad, the media presence of polka music has been crucial to its diffusion. In the 1940s and 1950s, polka enjoyed a high profile in American mass media. By the 1990s this presence was reduced to next to nothing. The advent of digital media has generated new platforms for the creation and sharing of polka music: internet radio, cable and satellite TV, and on-line videos. These new media have changed the nature of the interaction of communities of polka enthusiasts.